PENERAPAN PRINSIP-PRINSIP EVALUASI PEMBELAJARAN PADA MATA PELAJARAN AL-QUR’AN-HADITS - Muhammad Arjuna S; Fajri Ismail; Husnah Lutfiah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
The purpose of this research is to find out how the application of the principles of learning evaluation is carried out in MA Aulia Cendikia. Knowing how the application of the principles of learning evaluation is carried out, it is expected to serve as an evaluation material to improve the quality of education. This research uses descriptive research method, with qualitative approach through observation, interview and documentation using Datan Miles and Huberman analysis techniques. The results of this research are the principles of learning assessment has been conducted, including the principle of integration, pedagogical principles, accountability principles, contingency principles, cooperative principles and there is a principle that is not able to apply in learning assessment activities such as the principle of objectivity.Factors that influence the application of learning evaluation principles to improve student learning outcomes in Al-Qur'an Hadith MA Aulia Cendikia Palembang subject are school administration policies that require teachers to create learning evaluation plans, motivation, teacher's ability to master the material, limited learning hours, teacher accountability and learning infrastructure that really needs to be considered to support this smooth process.